IMPLIKASI PELAYANAN PUBLIK DALAM PENERTIBAN PENDUDUK PENDATANG DI KOTA DENPASAR - I Nengah Merta (Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
Not yet vanished in shared memory that the Bali Bombing of October 12, 2002 killed hundreds of lives. The event had a big impact for the people of Bali. Uncontrolled migrant population is considered as one of the causes of the Bali bombing tragedy. The incident then made local governments more aware to exercise control over the presence of migrants (tamiu). The government is strict in controlling the immigrant population living in Denpasar by issuing a KIPP policy. KIPP as one of the public service practices required by the government of Denpasar City. What are the implications of public services in controlling immigrants? The purpose of this study is to understand the implications of public services in controlling the population of migrants. The research method uses descriptive qualitative research by involving government, media crew, migrant community leaders and academics as respondents. The findings of this study indicate that in practice KIPP services open opportunities for corruption, collusion, and nepotism. high cost public services. population data from the village, sub-district, district and city levels even to the provincial level are out of sync, social pathology is increasing. This paper will be very useful for structuring public service bureaucracy